Pensar cinema: o sistema crítico no cinema de retomada - Teixeira, Luiz Gustavo Vilela (2017)
If criticism is any reflection on a work, starting from this same work to generate relations of meaning that interfere with the enjoyment of those who interact with it, it is clear its impact and dimension as a promoter of crisis. Starting from this idea, this work undertakes a dip in the critical production produced on contemporary Brazilian cinema, said of Retomada, in order to analyze how the cinematographic reflection is structured. By choosing three films with strong metalinguistic articulation, it will be possible to see how the discourse on cinema manifests itself in their respective criticisms. Through the analysis of these texts, this work seeks to understand how critical thinking manifests itself and perceives cinema. To that end, I propose to conceptualize film criticism through its theoretical constitution in relation to the history of cinema, starting with authors such as André Bazin, Walter Benjamin and Jean-Claude Bernardet. Criticism is rethought in its collective dimension, forming itself as a critical system, as proposed by José Luís Braga. I also seek to conceptualize contemporary Brazilian cinema, inserting it in a historical context in relation to criticism, forms of production and reception of the public through the historical-critical accounts of authors such as Paulo Emílio Sales Gomes, Ismail Xavier, Marcelo Ikeda and Laurent Debois. This reference will be used as a basis to analyze the films raised - Lisbela and Prisioneiro (2003), Guel Arraes; Cinema, Aspirins and Urubus (2005), Marcelo Gomes; and Saneamento Básico, O Filme (2007), Jorge Furtado - in view of its context of production and launching, as well as their respective criticisms, in order to reflect on the constitution of contemporary film criticism and how it perceives Cinema de Resomada formulator of hypotheses about the cinema itself, both through punctual contributions and through its constitution as a system.